ENVIRONMENTAL EDUCATION IN THE INSTITUTIONS OF SUPPLEMENTARY EDUCATION IN OREL REGION - O. V. Aleksashkinа (Universitas Brawijaya, 2018)
Environmental education is one of the directions of the state policy of our time. The main idea of environmental education is to form the younger generation of a new system of values in communication with nature, responsible attitude to the environment, their health and the health of others, active socio-environmental position; creative translation of the values of environmental culture in the educational space, as well as in the formation of readiness and desire to have a positive impact on changes in the environmental situation in the world.